Randomized Controlled Trial of Polyethylene Glycol versus Oral Sodium Phosphate for Bowel Preparation in Unsedated Colonoscopy - Dong Yang; Ke Tao; Geng Chen; Luping Zhang; Qingying He; Hong Xu (Gastroenterology Research and Practice)
Aim. To identify the most effective laxative for bowel preparation in unsedated colonoscopy. Methods. Between April 2019 and April 2020, a total of 586 outpatients scheduled for unsedated colonoscopy at the First Hospital of Jilin University (Changchun, China) were randomized into one of two groups, namely, the polyethylene glycol (PEG) group or the oral sodium phosphate solution (OSP) group. The cleaning efficiency and other relevant clinical parameters were compared between the two groups. Results. Each group consisted of 293 patients. There were no significant differences in gender, body mass index, and history of abdominal surgery between the two groups. There were more cases of laxative intolerance in the PEG group than in the OSP group (7.5% vs. 0.7%, P<0.05). After tube insertion, we found that the cleaning efficiency of OSP was better than that of PEG (P<0.05). After cleaning, there was no significant difference in bowel cleanliness between the two groups (P>0.05). The colonoscopic insertion time of the PEG group was significantly shorter than that of the OSP group (10.0 vs. 12.0 min, P=0.002), and colonoscopic insertion was more difficult in the OSP group than in the PEG group (P=0.036). The VAS score of the PEG group patients was significantly lower than that of OSP group patients (4.0±1.3 vs. 5.2±1.7, P≤0.001). There were no significant differences in the cecal intubation rate and the detection rate of polyps and ulcers/erosion between the two groups. Conclusion. The cleaning efficiency and tolerability of OSP were preferable to those of PEG, but there was no significant difference in bowel cleanliness after washing the colon and suctioning the fluid. Compared with patients of the OSP group, those of the PEG group required a shorter colonoscopic insertion time and reported a more comfortable experience. Therefore, for cases that are tolerant of PEG, PEG is a better choice for unsedated colonoscopy.